PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP DISIPLIN KERJA PEGAWAI DI KANTOR KECAMATAN BAROS KABUPATEN SERANG - Muhamad Anid Hikmanudin; Khaeruman Khaeruman; Edi Muhammad Abduh (CV. ALIM'SPUBLISHING, 2024)
In the current era in an organization or institution, human resources (HR) are a very important component. For organizations or agencies, two factors that are worth studying in depth are leadership and organizational culture, which can increase employee motivation and commitment. And can uphold the values of Leadership, Organizational Culture and Work Discipline of employees at the Baros District Office, Serang Regency. The purpose of this research is to find out whether Transformational Leadership has an effect on employee work discipline, to find out whether Organizational Culture has an effect on employee work Discipline, to find out whether Transformational Leadership and Organizational Culture have an effect on employee work Discipline.The research method used in this research is a correlational quantitative approach. namely to test the influence of the independent variable on the dependent variable which in this research uses 2 independent variables (Transformational Leadership, Organizational Culture) and 1 dependent variable (Discipline). The approach used in this research is a survey method of 34 employees.The results of this research are that there is a significant influence of leadership on employee work discipline. Based on the calculation results of SPSS Version 27, the value of tcount > ttable (-4,939 > 1.693) is obtained, so H0 is rejected and H1 is accepted. And there is a significant influence of organizational culture on employee discipline. Based on the SPSS Version 27 calculation results, the value of tcount > ttable (13,102 > 1.693), H0 is rejected and H1 is accepted.Based on the significance test, the Fcount value was 99,220 and Ftable was 3.30. Based on the significance test, the Fcount value is greater than Ftable, so there is an influence between Leadership and Organizational Culture values on employee work discipline.